Volatile and non-volatile compounds and antimicrobial activity of Mansoa difficilis (Cham.) Bureau & K. Schum. (Bignoniaceae) - GUILHON, Giselle Maria Skelding Pinheiro (2013)
Essential oil from the leaves of Mansoa difficilis was analyzed by GC/MS. Oct-1-en-3-ol (49.65%) was the major compound, but diallyl di- and trisulfide were also present (0.85 and 0.37%, respectively), justifying the garlic-like odor of the crushed leaves. The hexane and methanol extracts of the leaves and stems afforded as main constituents a mixture of linear hydrocarbons, spinasterol, stigmasterol, ursolic and oleanolic acids, two apigenin derivatives and verbascoside. The hexane and methanol extracts of leaves were tested for antimicrobial activity against ten microorganisms. The hexane extract was active against both Psedomonas aeruginosa and Staphylococcus aureus.